-2x+8=-3(2x+4)

Simple and best practice solution for -2x+8=-3(2x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x+8=-3(2x+4) equation:


Simplifying
-2x + 8 = -3(2x + 4)

Reorder the terms:
8 + -2x = -3(2x + 4)

Reorder the terms:
8 + -2x = -3(4 + 2x)
8 + -2x = (4 * -3 + 2x * -3)
8 + -2x = (-12 + -6x)

Solving
8 + -2x = -12 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
8 + -2x + 6x = -12 + -6x + 6x

Combine like terms: -2x + 6x = 4x
8 + 4x = -12 + -6x + 6x

Combine like terms: -6x + 6x = 0
8 + 4x = -12 + 0
8 + 4x = -12

Add '-8' to each side of the equation.
8 + -8 + 4x = -12 + -8

Combine like terms: 8 + -8 = 0
0 + 4x = -12 + -8
4x = -12 + -8

Combine like terms: -12 + -8 = -20
4x = -20

Divide each side by '4'.
x = -5

Simplifying
x = -5

See similar equations:

| (4(f^4)^2f)/8f^10 | | 3(2x-8)-(-5x+10)+5(2-4x)-3x=10x-7 | | x^2-64x+620=0 | | 42x^2-5= | | 6/7(7y-14)=-9 | | 11x+67=5x+25 | | 501x-42y=3 | | x^2-6x+15=7 | | 6x-6y=48y | | x-45=x/4 | | 87x+12y=-14 | | 2(n-1)=2(3n-1) | | 6+4+x=9+1 | | -24-6x=-6(-2+3x) | | 4x(x)+20x+25=0 | | -3-5x=-2x-3(x+1) | | 3/7x-13=17 | | ln(x)-ln(3x)=3 | | 4x(x)+20x= | | 24x-60=60x-24 | | -7x-12=-2-6(1+x) | | 1/4(8x-20)=1/8(15x-6) | | 9(x+10)+4=-7(x-1)-3 | | -4(b-8)=32-4b | | 0.28=glox | | 0=380x-10500-x^2 | | 2y+3=8y-7 | | 9x+94=-7(x-1)-3 | | -6/5y-7=5 | | 5k-24=4(3k+8) | | 4x+6=x+1 | | 50x^3/10x |

Equations solver categories